Analysis of the drug package inserts in India as per the CDSCO guidelines - Vyas, Ansh P.; Gor, Alpa P. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: The package insert (PI) is provided along with the drug in its manufactured container by pharmaceutical companies. This is one of the ways to provide essential information related to drugs to healthcare professionals and patients. Pharmaceuticals follow the regulations mentioned in the drugs and cosmetics act (1940) and rules (1945) under Schedule D and the central drugs standard control organisation (CDSCO). Methods: A cross-sectional, observational, prospective study was conducted at Shree Krishna Hospital, Anand, Gujarat. From December 2023 to January 2024, a total of 98 PIs were collected from pharmacy stores within the hospital. All PIs were analyzed according to CDSCO guidelines. Results: A total of 98 PIs were analyzed. After the analysis,>90% of the information is present in half of the parameters. There is 25-65% information present regarding the drug details in the rest of the parameters. Conclusions: Our study has revealed that the information on package inserts is currently inaccessible. If drug companies can present this crucial information in a manner that is easily accessible to patients, it has the potential to greatly improve compliance. In our country, where concerns regarding the quality of medicines arise, implementing high-quality package inserts can effectively address these concerns.